Diseño de un dinamómetro de prony para un motor monocilíndrico de 2.4 HP para el laboratorio de motores de la UAN sede sur. (2023)
The purpose of this work is to design a prony dynamometer for a 2.4 HP single-cylinder engine for the UAN South headquarters laboratory. This with the objective of determining the performance of the single-cylinder engine based on output variables, such as power, torque and angular velocity.